1998
DOI: 10.4319/lo.1998.43.5.0799
|View full text |Cite
|
Sign up to set email alerts
|

Forms and availability of sediment phosphorus in carbonate sand of Bermuda seagrass beds

Abstract: Primary production by seagrasscs in tropical and subtropical carbonate sediments often appears to be phosphorus (P) limited, and several studies have sought to identify the possible sources of P for long-term growth. Here, we quantify concentrations of particulate and dissolved P and fluoride (F-) in carbonate sediments, sediment-water P exchange, and leaf-tissue P concentrations in three seagrass beds in Bermuda. We also present data on the sequential extraction of P and F-from the sediments at each site. Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
1
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 177 publications
(123 citation statements)
references
References 31 publications
3
111
1
8
Order By: Relevance
“…Note that these tropical carbonate systems may become N limited as anthropogenic nutrient enrichment accelerates and rates of P sorption decrease (McGlathery et al 1994;Howarth et al 1995;Jensen et al 1998). From his studies of N and P dynamics in lownutrient tropical lagoons, Smith (1984) was impressed at how P acted as the master variable, with N being responsive over time, just as was the case in the ocean system described by Redfield (1958) and the lake experiments described by Schindler (1977).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Note that these tropical carbonate systems may become N limited as anthropogenic nutrient enrichment accelerates and rates of P sorption decrease (McGlathery et al 1994;Howarth et al 1995;Jensen et al 1998). From his studies of N and P dynamics in lownutrient tropical lagoons, Smith (1984) was impressed at how P acted as the master variable, with N being responsive over time, just as was the case in the ocean system described by Redfield (1958) and the lake experiments described by Schindler (1977).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Pore-water pH and F 2 changes are suggested as proxies for sediment (specifically carbonate fluoroapatite) dissolution and have been used in laboratory experiments and in the field to determine P release (Rude and Aller 1991;Jensen et al 1998;Burdige and Zimmerman 2002). Our dissolution experiments showed that F 2 was liberated from sediment cores at high OA concentrations, but that increased F 2 concentrations were not present with equal H + additions in the form of HCl, suggesting that OA are more efficient at dissolving carbonate fluoroapatite minerals than simple changes in acidity (such as the acidity provided by OA-biotic mechanisms).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated total sediment dissolution rates and seagrass uptake rates and found that P i concentrations provided by rates of bulk sediment dissolution are not sufficient to relieve P-limitation (Jensen et al 1998;Gras et al 2003;Nielsen et al 2006). Recent evidence suggests that there are increased rates of sediment dissolution in marine rhizosphere sediments, and that high rates of oxidation caused by seagrass O 2 release may provide the required amount of acid to explain enhanced rates of dissolution (Ku et al 1999;Burdige and Zimmerman 2002;Burdige et al 2008).…”
mentioning
confidence: 99%
“…comm. ;Erftemeijer and Middelburg 1993;Jensen et al 1998). The shape of the profile is the net result of sources of PO 4 3Ϫ (mainly decomposition of organic matter and sediment dissolution), sinks of PO 4 3Ϫ (primarily uptake by seagrasses and sediment immobilization), and a loss of PO 4 3Ϫ (presumably dominated by molecular diffusion) to the water column and, to some extent, to the sediment below our measurements.…”
Section: Protocol For Sampling In Cores-mentioning
confidence: 99%
“…In previous studies, we have used sippers extensively for pore-water extractions from both vegetated and unvegetated carbonate sediments (McGlathery et al 1992, pers. comm;Jensen et al 1998). Part of our motivation for developing this new technique was the need to obtain porewater samples at a much finer depth resolution, to accurately estimate fluxes across the sediment-water interface and transformation rates of solutes within the sediments.…”
mentioning
confidence: 99%